Multimedia Pembelajaran Bahasa Arab Berbasis Blog, Website, dan Facebook - Mohammad Ihkam (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2018)
The urgent development of information technology has transformed the concept of computer-based education, information technology-based education. Information technology can integrate computers, the internet and other information system facilities into a tool that empowers the teaching and learning process to be more creative, innovative, and competitive. The use of Information Technology for education will shift the nature of university introvert to a more proactive extroversion. Likewise with smaller educational units such as faculties, departments, study programs, even for teachers and students. Therefore, the authors see the importance of developing Arabic language learning based on blogs, websites and Facebook, and the like. In order to attract the interest of the Islamic community, especially to learn Arabic. Multimedia can be defined as a collection of computer-based media and communication systems that have a role to build, store, deliver and receive information in the form of text, graphics, audio, video, and so on. Multimedia learning Arabic can be interpreted as a multimedia application used in the Arabic learning process. Blogs, websites, and Facebook can be used as Arabic learning media.For educational institutions, technology in blogs, websites and Facebook can be used as a medium to further improve the quality of distance learning. Multimedia support and the development of media in the internet world are increasingly helping to realize interactive learning, even though it doesn't meet physically.